FUZZY GROUPOIDS VERSUS LEFT INVARIANT FUZZY EQUIVALENCE RELATIONS - Mădălina Roxana BUNECI (Fiabilitate şi Durabilitate)
The purpose of this note is to highlight the relationship between T-fuzzy groupoids and left (or right) invariant T-fuzzy equivalence relations. We will also show that there is a 1 - 1 correspondence between the T-fuzzy reductions of a T-fuzzy groupoid and the T-fuzzy reductions of the associated T-fuzzy equivalence relation, as well as a similar correspondence between disjoint unions.